Entrance of the Suhaveshwar Temple - Temples of India Project Team (Jio Institute, 2024)
The east-facing elevation and principal entrance of the Suhaveshwar Temple. Suhveshwar Temple is fronted by a Nandi sculpture on a pedestal, but the superstructure of the mandapa (pillared hall) has fallen.